Description of Ophthalmolycus andersoni sp. nov. (Pisces, Zoarcidae) from the Antarctic Ocean - Matallanas, Jesús (Zootaxa, 2009)
A new species of zoarcid fish is described on the basis of three specimens collected from the Antarctic Peninsula, Antarctic Ocean. The new species can be distinguished from its congeners by its body shape and pigment pattern, and by the following combination of characters: 6 branchiostegal rays; pectoral-fin origin well below midbody, pectoral base extending ventrally to abdomen; lateral line double with ventral and medio-lateral branches; oral valve not reaching anterior edge of vomer; gill slit extending ventrally well below end of pectoral fin base; vertebrae asymmetrical 22+7074=92-96; dorsal fin origin associated with vertebrae 4 or 5 with no supraneurals; pectoral fin rays 16 or 17; 2 postorbital pores (positions 1 & 4) and 2 well developed pyloric caeca. The relationships of the new species with its congeners are discussed.